2022
DOI: 10.2174/1567202619666220414093130
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Ginsenoside Rg1 on LPS-Induced Septic Encephalopathy and Associated Mechanism

Abstract: Background: Sepsis frequently occurs in patients after infection and is highly associated with death. Septic encephalopathy is characterized by dysfunction of the central nervous system, of which the root cause is a systemic inflammatory response. Sepsis-associated encephalopathy is a severe disease that frequently occurs in children, resulting in high morbidity and mortality. Objectives: In the present study, we aim to investigate the neuroprotective mechanism of ginsenoside Rg1 in response to septic enceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This study also detected components in XXMD-C, including ephedrine, pseudoephedrine, cinnamaldehyde, baicalin, baicalein, wogonin, and ginsenoside Rg1, which can represent the four Chinese medicinal materials in XXMD-C. Many components in XXMD-C, such as ephedrine ( Zheng et al, 2012 ; Wu et al, 2014 ; Wei et al, 2019 ; Sioud et al, 2020 ), pseudoephedrine ( Li et al, 2019 ), cinnamaldehyde ( Liu et al, 2019 ; Kim et al, 2020 ; Gulec Peker and Kaltalioglu, 2021 ), baicalin ( Li et al, 2020 ; Fu et al, 2021 ; Yan et al, 2021 ), and ginsenoside Rg1 ( Chen et al, 2022 ; Zhang et al, 2022 ), have been reported in relevant literature to have significant anti-inflammatory effects. Therefore, it can be seen that XXMD-C indeed has anti-inflammatory potential.…”
Section: Disscussionsupporting
confidence: 64%
“…This study also detected components in XXMD-C, including ephedrine, pseudoephedrine, cinnamaldehyde, baicalin, baicalein, wogonin, and ginsenoside Rg1, which can represent the four Chinese medicinal materials in XXMD-C. Many components in XXMD-C, such as ephedrine ( Zheng et al, 2012 ; Wu et al, 2014 ; Wei et al, 2019 ; Sioud et al, 2020 ), pseudoephedrine ( Li et al, 2019 ), cinnamaldehyde ( Liu et al, 2019 ; Kim et al, 2020 ; Gulec Peker and Kaltalioglu, 2021 ), baicalin ( Li et al, 2020 ; Fu et al, 2021 ; Yan et al, 2021 ), and ginsenoside Rg1 ( Chen et al, 2022 ; Zhang et al, 2022 ), have been reported in relevant literature to have significant anti-inflammatory effects. Therefore, it can be seen that XXMD-C indeed has anti-inflammatory potential.…”
Section: Disscussionsupporting
confidence: 64%
“…Rg1 is the main active component of Panax ginseng and has many pharmacological properties [34]. In recent years, the protection afforded by Rg1 has been confirmed in sepsis [35] and sepsis-related diseases, including septic acute lung injury [36], septic cardiac dysfunction [37], and septic encephalopathy [38]. Additionally, several studies have demonstrated the beneficial role of Rg1 in many types of experimental models of renal disorders, such as obstructive nephropathy [39] and unilateral ureteral obstruction [40].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ginsenoside Rb1 improves inflammation in the heart, kidneys, and nervous system. In the nervous system, ginsenoside Rg1 can improve murine microglia and brain type I astrocytes damage through the NF-κB/TLR4 inflammatory signaling pathway and the p38/JNK-MAPK signaling pathway [225,226]. In a spinal cord injury and cognitive impairment-based study in rats, ginsenoside Rb1 improves injury and cognitive impairment via NRF2 and PI3K/AKT inflammatory signaling pathways [227,228].…”
Section: Panax Ginseng C a Meyer And Its Compounds Delay Cellular Agi...mentioning
confidence: 99%